2004
DOI: 10.1016/j.cardiores.2004.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Direct block of hERG potassium channels by the protein kinase C inhibitor bisindolylmaleimide I (GF109203X)

Abstract: In summary, PKC-independent effects have to be carefully considered when using BIM I as PKC inhibitor in experimental models involving hERG channels and I(Kr) currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 28 publications
2
19
2
Order By: Relevance
“…The hERG-inhibitor effect of bisindolylmaleimide I has been previously described by Thomas et al (2004b) presenting results very congruent with ours. The EC 50 value obtained in HEK cells was 0.76 µM in our, while 1 µM in their experiments.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The hERG-inhibitor effect of bisindolylmaleimide I has been previously described by Thomas et al (2004b) presenting results very congruent with ours. The EC 50 value obtained in HEK cells was 0.76 µM in our, while 1 µM in their experiments.…”
Section: Discussionsupporting
confidence: 92%
“…The EC 50 value obtained in HEK cells was 0.76 µM in our, while 1 µM in their experiments. 1 µM 11 bisindolylmaleimide I caused a 69.2 % inhibition in the native I Kr of guinea pig (Thomas et al 2004b) and a 69.4 % blockade of canine I Kr (present study). An interesting difference between the results of the two studies can be observed in the kinetic properties of I Kr blockade.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations